Dinamika masnih sistemov - Harl, Boštjan; Kegl, Marko; Karner, Timi (University of Maribor Press, 2024)
Dynamics of Mass Systems. This textbook deals with the dynamics of rigid-body mass systems. In the context of kinematics, the description of spatial motion in different coordinate systems is presented, as well as the rotation matrix and its parametrization, and Euler angles. This is followed by dynamics and a demonstration of the law of the rigid body momentum and rotational quantity. In the context of mechanical vibrations, the intrinsic and forced vibrations of single and multi-degree-of-freedom systems are discussed. The textbook concludes with an area of analytical mechanics, which includes the presentation of generalised coordinates, virtual work and generalised forces. Newton-Euler, Lagrangian and Hamiltonian approaches to the formulation of the equations of motion of systems and their numerical solution are presented.